Determination the Percentages of Microbial Contaminants in Crops and Livers by Using the Traditional and Backtrac 4300 Technology - Sudad J. Mohammed,; Qasim, Doaa Adel; Mousawi , Adil .T. Al – (International Journal of Psychosocial Rehabilitation, 2020)
Poultry meat, like other foods, is subjected to contamination from microorganisms during the process of manufacturing, storing, marketing and selling them if health measures are not taken, makes them a cause of diseases for the consumer, especially food poisoning, so this study came to examine poultry meat (livers and crops) available in Baghdadlocal markets. Fourteen samples of chicken meat were collected during 2019, including 7 liver samples and 7 crop samples. A serial dilution was made to estimate the level of microbial contamination including (coliform bacteria, Staphylococcus aureus, and Salmonella spp) by using traditional method and Back Trac technique.in all chicken samplesStaphylococcus aureus were detected, where the highest contamination in sample (Al-kawther) was (9×104) CFU/g in the livers while in crops was (6×104) CFU/g. The highest contamination with coliform bacteria was in the (Hanana) sample, in the livers was (8×102) CFU/g while in crops was (4×102) CFU/g, the results also indicated the samples of (Al-Bayader) and (Al-kawther) was positive for salmonella bacteria. While after examining the same samples with BackTrac device, the highest bacterial count was found in a sample (Al-kawther) when examining the bacteria of staphylococcus aureas, where the highest percentage (3.4 E+5) was in the liver, but in the crops the total count was (1.8 E+5) and the detection time was started at 8.80hrs, while coliform bacteria, was also found in a sample (Al-kawther), where the total number in livers (4.6 E+3) while in crops was (2.4 E+2),the detection time was started at 11.33hrs, the samples (Hanana) (Al-Bayader) (Al-kawther) were positive for detection the salmonella bacteria and the detection time was at 5.96 hrs.